Using ALNs to Support a Complete Educational Experience - Thompson, Melody M.; McGrath, Jean W. (Online Learning, 1999)
The most obvious factor influencing students’ satisfaction with distance learning is convenience of access. While ALNs clearly can provide convenient access to educational content, how do they measure up in terms of access to the broader range of elements that make up a “complete” educational experience? Within traditional education, a complete education has been viewed as inseparable from the resident experience, with its access to instructional as well as co-curricular activities and support services. ALN programs that hope to meet the educational— rather than merely informational—needs of distant students must find ways to offer comparable opportunities and services. Penn State’s World Campus is working to realize the potential of ALNs by using innovative strategies for meeting several specific objectives. These objectives include access to high-quality course content; interactions between faculty members and students beyond those in direct instruction; interaction among students at the program level; broad access to information and instructional resources; flexible access to appropriate support services; and developing students’ feeling of “belonging” to the institution. This paper provides specific examples of online strategies for meeting these objectives and reports preliminary evaluation results relating to student satisfaction in courses offered during the first two semesters of World Campus programming.